Comorbid psychiatric disorders in 201 cases of encopresis - Ünal, Fatih; Pehlivantürk, Berna (The Turkish Journal of Pediatrics, 2004)
Although encopresis is a common and complex disorder, relatively few studies have evaluated the comorbid psychiatric disorders in this condition. This study was performed to investigate the comorbid psychiatric disorders in encopresis. One hundred and sixty boys (79.6%) and 41 girls (20.4%) fulfilled the diagnostic criteria for encopresis according to DSM-IV. There was at least one comorbid diagnosis in 149 (74.1%) patients. The most frequent comorbid diagnosis was enuresis (55.2%). Clinical and demographical data were compared between patients with comorbid disorders and others. Primary encopresis was significantly more frequent in patients with comorbid disorders, and the mean age at admission was lower in these patients. The mean interval between the onset of symptoms and the diagnosis was significantly shorter in secondary encopretic patients with comorbid disorders. Furthermore, there were significantly more psychiatric disorders in the first-degree relatives of patients with comorbid disorders. Encopresis is frequently accompanied with a psychiatric disorder. Clinicians need to inquire about symptoms of other psychiatric disorders in patients who present with encopresis and vice versa.